Evaluation of Blood Parameters When Infected with Candida Albicansand Its Recovery Using Probiotics - Umniyahqays jasim; Dalia abdalkareem (Institute of Medico-legal Publications Pvt Ltd, 2022)
Purpose: To study, blood components and some indicators of liver function were measured andCandida albicans was isolated and identified from infected cows’ vagina with inflammatory signs then experimentally in rabbits treated with estradiol hormone. Introduction: Candidiasis is an infection caused by yeast,.Candida can multiply and cause an infection if the environment inside the vagina changes in a way that induces its growth.Materials and Methods: Isolation and identification of candida albicans isolate from cowʼ vaginitis (40 samples), duration in November 2020 till May 2021 then treated with saccharomyces cerevisiae. Candida albicans inoculums at 1.5 ×108 cell /ml, in non-pregnant vagainal’ Rabbits a weight (2 kg) after treated with estradiol hormone for several days before the infection occurred. The experiment was carried out in the microbiology laboratories in College Veterinary Medicine- the University of Baghdad, the blood, liver parameters, and rabbits’ vaginal histology was studied.Results: The Hb parameters in G2 showed higher significant differences ( 8.31±0.75107) compared with G1(12.80 ± 2.42782), G3 (13.26 ± 1.465), G4 (12.46 ± 1.987), G5 (12.75 ± 2.128) respectively, the effectiveness of the treatment with S.cerevisiae and its ability to return hemoglobin and liver functions to its normal value and the treatment cause inhibitory effect of C.albicans infection, the vagainal histological section in G4 showed narrow folding of mucosa thrown with mild MNCs infiltrate LP and submucosa, no inflammatory cells seen in a muscular layer or in the serosa. Conclusion: The study proved the effectiveness by using Saccharomyces cerevisiae and treating rabbits vaginal infection with pathogenic Candida albicans, that Injected estradiol hormone Sthen, recovery the blood and liver parameters to their normal condition, in addition, the treatment of vaginal tissue and its return to its normal state